All Questions Topic List
UNKNOWN Questions
Previous in All Question Next in All Question
Previous in UNKNOWN Next in UNKNOWN
Question Number 63865 by mmkkmm000m last updated on 10/Jul/19
If∫4ex+6e−x9ex−4e−xdx=Ax+Blog(9e2x−4)+C,then
Commented by kaivan.ahmadi last updated on 10/Jul/19
(Ax+Blog(9e2x−4))′=4ex+6e−x9ex−4e−xbutthelefthandsideisequaltoA+B×18e2x9e2x−4×1ln10=A+Bln10×18ex9ex−4e−x=9Aexln10−4Ae−xln10+18Bexln10(9ex−4e−x)=(9A+18ln10B)ex−4Ae−x9ex−4e−x⇒{4A=6⇒A=329A+18ln10B=4⇒18ln10B=−192⇒B=−19ln1036
Commented by mathmax by abdo last updated on 10/Jul/19
letI=∫4ex+6e−x9ex−4e−xdx[⇒I=∫4e2x+69e2x−4dxchangemente2x=tgiveI=∫4t+69t−4dt2t=∫2t+3t(9t−4)dtletdecomposeF(t)=2t+3t(9t−4)F(t)=at+b9t−4a=limt→0tF(t)=−34b=limt→49(9t−4)F(t)=2×49+349=8+274=354⇒F(t)=−34t+354(9t−4)⇒I=∫(−34t+354(9t−4))dt=−34ln∣t∣+3536ln∣9t−4∣+c−34(2x)+3536ln∣9e2x−4∣+c=−32x+3536ln∣9e2x−4∣+c⇒A=−32,B=3536andC=c.
Terms of Service
Privacy Policy
Contact: info@tinkutara.com